Analysis of Economic Recovery Programs Through Grants from the National Disaster Management Agency Using the Social Return on Investment Method - Salsabila, Sayyid; Jajuli, M. Sulaeman; Sudrajat, Budi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study evaluates the economic recovery program for tsunami survivors, focusing on the benefits provided by stakeholders. It examines the financial aspects that yield economic, environmental, social, and cultural benefits. The research questions addressed are: (1) How effective is the Economic Recovery Program through Grant Assistance for Tsunami Disaster Survivors? (2) How does the Social Return on Investment (SROI) framework apply to the economic recovery program? (3) What is the impact of the program based on SROI evaluation? This study employs a quantitative approach, utilizing observation and documentation for data collection. The analysis involves numerical data interpretation, assessing the developmental progress over time. Findings indicate that the economic recovery program has an SROI ratio of 4.27:1, demonstrating a benefit value 4.27 times greater than the investment made.